Development and Validation of Person-Centered Cut-Points for the Figure-of-8-Walk Test of Mobility in Community-Dwelling Older Adults. (1st February 2020) - Coyle, Peter C; Perera, Subashan; Shuman, Valerie; VanSwearingen, Jessie; Brach, Jennifer S
Abstract: Background: The Figure-of-8-Walk test (F8WT) is a performance measure of the motor skill of walking. Unlike walking speed over a straight path, it captures curved path walking, which is essential to real-world activity, but meaningful cut-points have yet to be developed for the F8WT. Methods: A secondary analysis of 421 community-dwelling older adults (mean age 80.7 ± 7.8), who participated in a community-based exercise clinical trial, was performed. Area under receiver operating characteristic curves (AUROCC) were calculated using baseline data, with F8WT performance discriminating different self-reported global mobility and balance dichotomies. Cut-points for the F8WT were chosen to optimize sensitivity and specificity. For validation, F8WT cut-points were applied to postintervention F8WT data. Participants were called monthly for 12 months after intervention completion to record self-reported incident falls, emergency department visits, and hospitalizations; risks of the outcomes were compared between those who performed well and poorly on the F8WT. Results: F8WT performance times of ≤9.09 seconds and ≤9.27 seconds can discriminate those with excellent (sensitivity = 0.647; specificity = 0.654) and excellent/very good global mobility (sensitivity = 0.649; specificity = 0.648), respectively. A total number of steps ≤17 on the F8WT can discriminate those with excellent/very good/good global balance (sensitivity = 0.646; specificity = 0.608). Compared to those who performed poorly, those who performed well had a lower incidence of negative outcomes: F8WT time ≤9.09 seconds = 46%–59% lower; F8WT time ≤9.27 seconds = 46%–56% lower; F8WT steps ≤17 = 44%–50% lower. Conclusions: Clinicians may consider these preliminary cut-points to aid in their clinical decision making, but further study is needed for definitive recommendations.